Economical evaluation of sludge reduction and characterization of effluent organic matter in an alternating aeration activated sludge system combining ozone/ultrasound pretreatment. (February 2015) - Yang, Shan-Shan; Guo, Wan-Qian; Chen, Yi-Di; Wu, Qing-Lian; Luo, Hai-Chao; Peng, Si-Mai; Zheng, He-Shan; Feng, Xiao-Chi; Zhou, Xu; Ren, Nan-Qi
Highlights: AAMA + O3 /US2# system was economically feasible that can give a 14.04% saving of costs. 55.08% sludge reduction was achieved in AAMA + O3 /US2# system compared with AAMA1# . Less humic substance and soluble microbial products were generated from AAMA + O3 /US2# . NH4 + -N removal and TTC-ETS activities showed significant positive correlations. Appropriate sludge lyses recycling gave rise to the improvement in microbe activity. Abstract: An ozone/ultrasound lysis–cryptic growth technology combining a continuous flow anaerobic–anoxic–microaerobic–aerobic (AAMA + O3 /US) system was investigated. Techno-economic evaluation and sludge lyses return ratio ( r ) optimization of this AAMA + O3 /US system were systematically and comprehensively discussed. Economic assessment demonstrated that this AAMA + O3 /US system with r of 30% (AAMA + O3 /US2# system) was more economically feasible that can give a 14.04% saving of costs. In addition to economic benefits, a 55.08% reduction in sludge production, and respective 21.17% and 5.45% increases in TN and TP removal efficiencies were observed in this AAMA + O3 /US2# system. Considering the process performances and economic benefits, r of 30% in AAMA + O3 /US2# system was recommended. Excitation–emission matrix and Fourier transform infrared spectra analyses also proved that less refractory soluble microbial products were generated from AAMA + O3 /US2# system. Improvement in 2, 3, 5-triphenyltetrazolium chloride electron transport system (TTC-ETS) activity in AAMA + O3 /US2# further indicated that a lower sludge lyses return ratio stimulated the microbial activity.